(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
This paper examines the design, implementation, and continuous improvement of a successful mentoring program integrated into cybersecurity capstone courses at Kennesaw State University, aimed at bridging the gap between academic learning and real-world experience. Faced with a need to implement experiential outcomes for cybersecurity graduates, the university introduced a structured mentoring initiative involving industry executives and technical leads to enhance students’ professional development, networking opportunities, and practical skills. The program’s structured approach to integrating industry mentorship has contributed to enhanced student engagement and provided valuable experiential learning opportunities. A continuous improvement process, anchored by after-action reviews at the end of each semester, allows the program to evolve in response to participant feedback, ensuring alignment with educational goals and addressing diversity, equity, and inclusion (DEI) challenges in the field. The paper concludes that this mentoring initiative offers students the opportunity to improve outcomes and underscores the importance of integrating experiential learning opportunities within academic curricula. Recommendations for institutions adopting similar programs include prioritizing mentor selection and training, implementing continuous feedback loops, and emphasizing mentor commitment to maximize student benefits.